Spa tourism statistics in the Kingdom of Yugoslavia - Radović - Stojanović, Jelena; Gnjatović, Dragana (Hotel and Tourism Management, 2021)
The paper presents statistical data on spa tourism in the Kingdom of Yugoslavia in the period from 1926 to 1940. The sources of data for the research were the Statistical Yearbooks of the Kingdom of Yugoslavia. The paper aims to show how spa tourism statistics and tourism statistics in general developed in the years between the two world wars. Furthermore, the paper aims to provide a picture of the level of development of spas and spa tourism in the Kingdom through the presented data. Illustrative data on hotel capacities for some of the most famous spas in the Kingdom of Yugoslavia are presented. A combination of historical and statistical methods was used to analyze statistical data on spa tourism and the financial effects of tourism. The existing data made it possible to calculate the share of revenues from spa tourism in both the total revenues from tourism and the national income of the Kingdom of Yugoslavia.